MOTIVASI PERSERTA DIDIK DALAM PEMBELAJARAN SEPAK BOLA DI SMP NEGERI 24 PONTIANAK - Sastra Junardi; Andika Triansyah; Edi Purnomo Edi Purnomo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractIn this study the motivation of students when learning soccer. The problem in this study is not yet known how much the motivation of students in soccer learning at SMP Negeri 24 Pontianak. The purpose of this research is to find out how much the motivation of students in learning soccer.The method used in the research is quantitative descriptive with survey techniques while the research subjects are grade VIII students of SMP Negeri 24 Pontianak with a total of 64 people.The results showed that the motivation of students at the time of learning soccer in SMP Negeri 24 Pontianak was very good category with a value of 207-238 with a frequency of 70 or a percentage of 70%. Good category 175-206 with a frequency of 30 with a percentage of .30%, the level of intrinsic motivation students when learning soccer where the category is very good 109-125 with a frequency of 55 and the percentage of 55,% good 92-108 with a frequency of 45 percentage 45,% ,, The level of extrinsic motivation of students when learning football where the category is very good 98-112 with a frequency of 53 and a percentage of 53%, both 83-97 with a frequency of 47 percent, 47%. Keywords: Student Motivation, Soccer Learning